Trace elements and the thyroid - Zhou, Qing; Xue, Shuai; Zhang, Li; Chen, Guang (Frontiers in Endocrinology, 2022)
Trace elements, such as iodine and selenium (Se), are vital to human health and play an essential role in metabolism. They are also important to thyroid metabolism and function, and correlate with thyroid autoimmunity and tumors. Other minerals such as iron (Ir), lithium (Li), copper (Co), zinc (Zn), manganese (Mn), magnesium (Mg), cadmium (Cd), and molybdenum (Mo), may related to thyroid function and disease. Normal thyroid function depends on a variety of trace elements for thyroid hormone synthesis and metabolism. These trace elements interact with each other and are in a dynamic balance. However, this balance may be disturbed by the excess or deficiency of one or more elements, leading to abnormal thyroid function and the promotion of autoimmune thyroid diseases and thyroid tumors.The relationship between trace elements and thyroid disorders is still unclear, and further research is needed to clarify this issue and improve our understanding of how trace elements mediate thyroid function and metabolism. This paper systematically reviewed recently published literature on the relationship between various trace elements and thyroid function to provide a preliminary theoretical basis for future research.